The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1348/135532507x267040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sexual interest using a choice reaction time task and priming: A feasibility study

Abstract: Purpose. We investigated the feasibility of assessing sexual interest in hetero-and homosexual men using two information-processing methods, namely a choice reaction time task and priming. The participants were expected to have longer reaction times for sexually explicit when compared with non-explicit pictures due to sexual contentinduced delay. In addition, the reaction times of the heterosexual (N ¼ 15) and homosexual (N ¼ 11) men for pictures corresponding with their sexual interest were compared to pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
5
18
2
Order By: Relevance
“…In line with prior findings by Santtila et al (2009), cognitive priming failed to bring about any substantial effects: The subliminal presentation of pictures prior to the target stimulus did not modify the CRT effect in any way. In particular, the idea that cognitive priming might amplify CRT responses was not supported.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with prior findings by Santtila et al (2009), cognitive priming failed to bring about any substantial effects: The subliminal presentation of pictures prior to the target stimulus did not modify the CRT effect in any way. In particular, the idea that cognitive priming might amplify CRT responses was not supported.…”
Section: Discussionsupporting
confidence: 88%
“…This means that there was no evidence of habituation modulating the CRT effect. This was somewhat surprising as the number of trials in the present experiment was higher than in Santtila et al (2009) found a weak non-linear trend with reactions becoming increasingly faster towards the later phases of the experiment. A possible explanation for this acceleration could be that the subjects lost their motivation and made rapid responses in order to arrive at the end of the experiment as soon as possible.…”
Section: Discussioncontrasting
confidence: 75%
“…Thus, in a classical design, the frequently found longest latencies for the preferred category were likely to be the result of both the task demands and, to a lesser extent, the automatic processes triggered by the stimuli running in the same direction. These additive effects under the constraint that the participant performed the task according to the implied self-perspective may help explain the superior ability of viewing time tasks to differentiate between groups of contrasting sexual preference (Areas-Under-the-Curves (AUCs) between .80 and 1.00; Imhoff et al, 2010) compared to other indirect measures assumed to tap into automatic processes triggered by sexually preferred stimuli, such as the Choice Reaction Time (AUCs between .60 and .83; Santtila et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Participants exhibit longer response latencies in CRT tasks when the pictures show sexually attractive individuals. CRT tasks have been shown to measure sexual orientation in a smaller number of studies (Santtila et al, 2009;Wright & Adams, 1994;1999). However, Santtila and colleagues reported methodological difficulties as they found the CRT to be a valid measure of sexual preference only when a subset of measures was taken into account.…”
Section: Task-irrelevant Measuresmentioning
confidence: 99%
“…Moreover, the CRT was not significantly correlated to the other two measures, whereas the IRAP and VT were significantly associated with each other at a substantial level and in the 3 In order to control for possible habituation or practice effects (as discussed by Santtila et al, 2009) due to the high number of trials in the present CRT, we also conducted all analyses separately for the first 108 and second 108 trials. The pattern found in the analysis of all trials still held for both halves of trials, with significant main effects of Age and Sexual Orientation, but no significant two-way or three-way interactions were obtained.…”
mentioning
confidence: 90%